Protective effect of increasing doses of famotidine, omeprazole, lansoprazole, and melatonin against ethanol-induced gastric damage in rats - (:unkn) unknown (My University, 2004)
Objective: To study whether the increasing doses of omeprazole, lansoprazole and famotidine afford protection against ethanol-induced gastric damage and to compare their antioxidant effect with that of melatonin. Material and Methods: Mucosal damage was evaluated by macroscopic examination and by the measurement of lipid peroxidation (LPO), glutathione (GSH) levels and myeloperoxidase (MPO) activity. Results: Ethanol administration-induced significant gastric damage, increased gastric acidity, and LPO and MPO activities, while tissue GSH levels decreased. The antiulcer drugs decreased the gastric acidity in a dose-dependent manner, whereas melatonin had no effect on this parameter. Biochemical parameters of oxidative damage, namely gastric LPO and GSH levels and MPO activities were reversed by both the antiulcer drugs and melatonin in a dose-dependent manner. Conclusion: These findings suggest that, parallel to increased acidity, reactive oxygen species have an important role in the pathogenesis of ethanol-induced gastric damage, and that melatonin, famotidine, lansoprazole and omeprazole are protective by their antioxidant property. However, according to our findings, inhibition of acid secretion is as important as the inhibition of oxidative damage in affording protection against ethanol-induced damage, and in this aspect melatonin seemed to be less efficient than the antiulcer drugs.
Keywords: Free radical scavengers; H2 receptor blocker; Proton pump inhibitors